ECO-CONSCIOUS CHOICES: EXAMINING THE EFFECTS OF GREEN MARKETING AND PRODUCT DESIGN ON CONSUMER INTENTIONS TO PURCHASE SUSTAINABLE PRODUCTS - Adwimurti, Yudhistira; Rahmani, Hani Fitria; Lumbantobing, Sabar Pardamean; Risa, Nurma (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to analyze green marketing and green product design on green purchase intention. This research uses a quantitative approach using primary data through an online questionnaire. The research population and sample are all consumers who use Green Wash brand detergent products spread across 3 (three) ASEAN countries, namely Indonesia, Malaysia and Thailand, with the unit of analysis being household consumers who were observed in April - June 2023, where samples were taken using a purposive technique. sampling with the number of samples used in the research being 100 respondents. The research was carried out using research data quality testing methods, research hypothesis testing and multiple linear regression testing using the SPSS Ver program. 26.The test results show that green marketing and green products have no effect on green purchase intention.